Developing Mental Skills in Youth Athletes. (18th March 2021) - Thompson, Melissa; Hilliard, Alisha
Abstract : Youth sport coaches have an incredibly complex and challenging role. The physical developmental changes that youth and adolescents go through can seemingly happen overnight. It is not surprising, therefore, that coaches spend most of their time thinking about how to help players with their physical skills. However, the significant developmental changes (e.g. cognitive, social, and emotional) that are happening just below the surface are equally as important and may be the key to an athlete improving. The purpose of this article is to describe how coaches can incorporate strategies for developing mental skills in a youth sport setting. Three areas, cognitive, social, and emotional development, are discussed with specific strategies for how to coach when working with youth across various sport settings. In considering each of these areas of development, critical milestones are highlighted with a short discussion of how those milestones might impact youth sport coaching. The article also provides suggestions on how to teach mental skills to youth. Finally, a season-long planning tool for incorporating mental skills into training is discussed. Ultimately, understanding how athlete development should impact your coaching and how you can train mental skills are two areas that can improve your effectiveness as a coach.